Bibliometric Map of STEM-Physics Research Evolution - Vivi Mardian; Judhistira Aria Utama; Irma Rahma Suwarma (Berkala Ilmiah Pendidikan Fisika, 2023)
STEM learning may increase students' engagement in the instructional process. STEM has a significant role in students' cognitive and skills development. STEM in the learning process is characterized as engaging and interesting actions that are structured in such a way. STEM research in physics has been conducted for the past two decades. However, the evolution of this research has not specifically explained the trend of STEM studies in learning, so a distribution map is needed from this research. A bibliometric research analysis was employed to determine research development in STEM learning on physics. The papers were collected from 2013 to 2022 by writing the title (STEM) and keywords (STEM, Physics) through Publish or Perish. In addition, the selected paper must also be in English and indexed by Scopus. The total number of final papers analyzed in this study was 169. In addition, VOSviewer shows that there are still many opportunities for future researchers to study STEM, especially those related to barriers, case studies, scientists, stem content, opinions, stem activities, stem fields, and programs. This study discovered that the topic of study of STEM has a good likelihood of being explored and that it can be combined with various fields to make the research unique.